Integration of Bengkalis Malay Bara’an Tradition Values for Character Strengthening in Islamic Religious Education Learning - Harmaini, Harmaini; Jarir, Jarir; Uri, Fatimah; Susanti, Elya (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the Study: This study aims to explore the Bara’an tradition of the Bengkalis Malay community and analyze its character values to be utilized as a source for strengthening character education in Islamic Religious Education learning at schools. Methodology: This research employs a qualitative approach with an analytical-descriptive method. The study was conducted in Pangkalan Batang Village, Bengkalis District, Bengkalis Regency, Riau Province. Data were collected through field studies, literature reviews, and interviews, which were then analyzed in accordance with the research objectives. Main Findings: The findings reveal that the Bara’an tradition is similar to halal bi halal but has unique local adaptations in Bengkalis. The tradition involves handshaking and seeking forgiveness, sharing meals, reciting shalawat (Marhaban), and concluding with a prayer led by an imam or group leader. The core character values reflected in the Bara’an tradition include religiosity, nationalism, independence, mutual cooperation, and integrity, which align with Indonesia’s national character education framework. Novelty/Originality of this Study: This study provides a new perspective on integrating indigenous Malay traditions into character education, specifically in Islamic Religious Education learning. It offers a thematic integration model, demonstrating how traditional cultural values can be systematically incorporated into the Islamic Religious Education curriculum to strengthen students' moral and ethical development.